2000
DOI: 10.1007/s001130050525
|View full text |Cite
|
Sign up to set email alerts
|

Gipsruhigstellung versus Vakuumstützsystem

Abstract: In a prospective randomized trial the early functional results after immobilisation in a cast were compared to those after using a vacuum stabilizing system. The vacuum stabilizing system Vacoped offers equivalent stability compared to a plaster cast. In contrast to the cast the Vacoped can be removed for body care and physical therapy. Additionally the range of motion for dorsal flexion/extention in the upper ankle joint can be adjusted. From 9/1996 to 7/1997 there were 40 patients included in the study with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…• 8 studies (412 participants) 7,16,20,22,35,36,39,41 were pooled for outcome at 9 to 12 wk postoperation • Statistically significant difference in favor of early ankle movement, but this was a small mean difference of 1.9° of dorsiflexion (95% confidence interval: 0.5°, 3.3°; P = .008; I 2 = 46%)…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…• 8 studies (412 participants) 7,16,20,22,35,36,39,41 were pooled for outcome at 9 to 12 wk postoperation • Statistically significant difference in favor of early ankle movement, but this was a small mean difference of 1.9° of dorsiflexion (95% confidence interval: 0.5°, 3.3°; P = .008; I 2 = 46%)…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…• 7 studies (369 participants) were pooled for outcome at 9 to 12 wk postoperation • An estimate was not calculated due to the very high levels of statistical heterogeneity (I 2 = 87%) • 3 studies 22,36,41 found statistically significant differences in favor of early ankle movement compared to immobilization • 4 studies 7,16,20,39 found no difference between treatment groups…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations